Integration of Local Wisdom in Web-Based Science Teaching Materials: Hots and Cultural Caring Attitudes Analysis - Hikmawati, Hikmawati; Suastra, I Wayan; Suma, Ketut; Sudiatmika, A A Istri Agung Rai; Rohani, Rohani (Journal of Science and Science Education, 2025)
The purpose of this study was to analyze the effect of web-based science teaching materials with the context of local wisdom on higher-order thinking skills (HOTS) and cultural care attitudes of students. The non-equivalent post-test-only control group design is the quasi-experimental design used. The study population included 140 grade VII SMPN 16 Mataram students, with a total sample of 35 students in the experimental class and 35 people in the control class. Data were obtained from the HOTS test instrument and a cultural caring attitude questionnaire which were analyzed using one-way MANOVA descriptive statistics. The HOTS test consists of 20 multiple-choice questions and a cultural care attitude questionnaire with 12 statements. The results showed that the average HOTS score of students in the experimental class was 83.75 while in the non-experimental class (the control class) it was 74.29. The average value of students' cultural attitudes in the experimental class was 91.61 while in the control class, it was 88.39. This means that HOTS and students' cultural care attitudes are superior in the experimental class compared to the control class. Based on the Multivariate tests, an F value of 20.32 was obtained with a significance much less than 0.05. This means there were differences in HOTS and cultural awareness between students who used web-based science teaching materials in the context of local wisdom and those who used conventional science teaching materials. Thus, using web-based science teaching materials in the context of local wisdom has an effect on HOTS and the attitude of caring for the culture of students. Web-based science teaching materials with the context of local wisdom can be an alternative contextual learning resource that plays an important role in strengthening character education, especially caring attitudes.